Qoheleth’s Ecocentrism and Hebel in Ecclesiastes 3: 16 – 22: Restoring Order to the Created World - Uchechukwu Oguike, Augustin Somé & (Asian Horizons, 2024)
The human person has long considered herself/himself to be the centre of creation. The Scriptures tend to affirm this from the creation story in Genesis, where the first humans were created in God’s own image and likeness, and given dominion over the earth (Genesis 1: 27 - 31). This notion of dominion over the earth has since been distorted, and humans have taken a destructive domineering stance over all other forms of creation; including plants and animals. The human condition has driven its agenda over the ages into becoming homo-dominus over all creation. Qoheleth, the Hebrew sage, thinks overwise. A critical, exegetical, ecological reading of the poetic-prose of Ecclesiastes 3: 16 – 22, reveals evidence of a wise man’s apprehension over the destructive tendencies of domineering humans over other forms of creation. Qoheleth is centuries ahead of the Church and Pope Francis’ Laudato Si’ as he sounds an ecological clarion call to all of humanity to desist from anthropocentricism that is neither beneficial to the human race nor promotes the will of God on earth. Qoheleth sounds this warning using his concept of Hebel, vanity!